Depression, Hopelessness and Risk of Suicide in patients Undergoing Hemodialysis: A Cross Sectional Study (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Hemodialysis (HD) is associated with organic difficulties and also causes changes in psychological status of patients. Depression is the most common and probably the most important psychopathological complication in in hemodialysis patients. Hopelessness was reported as the aggravating factor of depression. Suicide is established as prevalent mental health problems in patients undergoing hemodialysis.Aim: To assess depression, hopelessness and risk of suicide in patients undergoing hemodialysis.Methods: A cross-sectional study was carried out among 50 hemodialysis patients at tertiary care hospital in India. Scales like Patients health questionnaire-9(PHQ-9), Beck’s hopelessness scale (BHS) and Columbia-suicide severity rating scale(C-SSRS) were used to assess depression, hopelessness and risk of suicide.Result: Out of 50 patients, 38(76%) showed depression, 40(80%) showed hopelessness and 4(8%) showed risk of suicide. There is a significant correlation between sessions of hemodialysis with depression (p value=
Keywords: Depression; Hopelessness; Risk of Suicide; Undergoing Hemodialysis; Cross Sectional Study Introduction